2014
DOI: 10.1063/1.4873537
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality-induced insulator-metal crossover in layered nickelates Lan+1NinO2n+2 (n = 2, 3, and ∞)

Abstract: Low-valence layered nickelates are a structural analog to the superconducting cuprates and possess interesting properties. In this work, we have systematically studied the electronic structure of Lan+1NinO2n+2 using first-principles calculations. Our results reveal that the Ni-3d 3z2 − r2 orbital state is active and evolves from discrete molecular levels to a continuous solid band and its filling varies as the dimensionality (or n) increases. The two-dimensional (2D) La3Ni2O6 and La4Ni3O8 are thus found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Although there have been few studies on the higher order R-P oxides for electrocatalysis, initial results have shown great promise. [100,141]…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…Although there have been few studies on the higher order R-P oxides for electrocatalysis, initial results have shown great promise. [100,141]…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…Available transport data indicate that LaNiO 2 is not a charge-transfer insulator [6,7] and there is no experimental evidence for antiferromagnetic order in any RNiO 2 material [8]. Electronic-structure calculations of LaNiO 2 indicate significant differences from CaCuO 2 due to the presence of low-lying La 5d states, as well as an increased splitting between Ni d and O p levels [9][10][11].…”
mentioning
confidence: 99%
“…[8][9][10] Pardo et al 11 anticipated that the pressure induced metal to insulator transition takes place at zero temperature and high−spin state to low−spin state transition at 105 K. Also La 4 Ni 3 O 8 can either be in ferromagnetic−metallic low spin (LS) phase or an antiferromagnetic−insulating high spin (HS) phase. Dimensionality induced insulator to metal transition was reported by Liu et al 8 in La n+1 Ni n O 2n+2 system as its dimensionality changes with variation with n (n = 2, 3 and ∞). The magnetic properties of this material series are determined by the spin states of Ni + and Ni 2+ .…”
Section: Introductionmentioning
confidence: 99%